(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The principles expressed in this research concern the poet’s artistic mastery and the translator’s stylistic approach within a comparative analytical framework. When discussing poetic translation, it is important to emphasize that the translator’s style becomes evident through the expression of the author’s stylistic features; in other words, “When the translator attempts to render the state of becoming one with the author’s persona, he simultaneously creates his own style on the basis of his mastery.